Evolution of self-care in patients with heart failure at the first outpatient return and three months after hospital discharge - Debora Cristine Previde Teixeira da Cunha; Lidia Aparecida Rossi; Carina Aparecida Marosti Dessote; Fabiana Bolela; Rosana Aparecida Spadoti Dantas
Objective: to analyze the evolution of self-care in hospitalized patients with decompensated heart failure, between the first return after hospital discharge (T0) and three months after this assessment (T1). Method: an observational, analytical and longitudinal study carried out in the cardiology outpatient clinics of two public hospitals in Ribeirão Preto, São Paulo. The sociodemographic and clinical data were collected through interviews and consultation of medical records. Self-care was assessed using the Brazilian version of the Self-Care of Heart Failure Index-SCHFI instrument. The data were analyzed by means of the Student's t test and paired distribution (McNemar) with a significance level of 0.05. Results: we verified an increase in the mean scores of the three subscales of SCHFI (Maintenance, Management and Confidence), when comparing the values of T0 and T1, these differences being statistically significant (p<0.001). When comparing the positive changes in self-care actions over these months, we found statistically significant changes in the Maintenance (6 out of 10 items), Management (5 out of 6 items) and Confidence (4 out of 6 items) subscales. Conclusion: self-care for heart failure improved in the period between the first return after discharge and the end of three months of follow-up. Further studies are needed to verify the variables associated with improved self-care after hospitalization.